The effect of A-PRP-therapy on reparative regeneration of bone tissue with acute bone fractures of the limbs - A. N. Blazhenko; I. A. Rodin; O. N. Ponkina; M. L. Mukhanov; A. S. Samoilova; A. A. Verevkin; V. V. Ochkas; R. R. Aliev (Инновационная медицина Кубани)
Objective. To evaluate the effect of A-PRP-therapy on reparative bone regeneration in acute limb bone fractures. Material and Methods. The study consisted of two parts – in the first part we studied the effect of A-PRP-therapy on the model of a comminuted fracture created in the operating room, an experimental study conducted on 40 Mature rabbits of the Flander breed, all animals were divided according to the principle of analogues into 2 groups (20 animals): in the study group – on the 5th day after osteotomy, platelet-rich plasma was injected into the fracture area, in the comparison group – the fusion occurred without the influence of any drugs. The second part presents the results of clinical testing of A-PRP-therapy, analyzed the results of treatment of 16 women with low-energy fractures of the distal radius metaepiphysis. The study group consisted of 6 patients whose surgical treatment was supplemented by A-PRP-therapy on 7, 14 days after surgery. The control group consisted of 10 patients who underwent surgical treatment without A-PRP-therapy.Results. The use of platelet-rich plasma to stimulate reparative osteogenesis in accute fractures reduces the time of fracture consolidation by 9.5 ± 1.1%.Conclusion. Platelet-rich plasma (PRP) to stimulate reparative osteogenesis is an inexpensive, easy to perform and effective alternative to the methods considered. The possibilities of application of this technology in traumatology and orthopedics require further research in order to create protocols for the use of PRP-therapy to stimulate the maturation of bone calluses.